Abciximab bolus with optional infusion in intervention for ST-elevation myocardial infarction. (August 2013) - Berglund, Ulf; Nilsson, Lennart; Janzon, Magnus
Abstract: Objectives . The standard abciximab regimen is a bolus dose followed by a 12-h infusion. Whether the bolus dose alone is sufficient for ST-elevation myocardial infarction patients receiving a high loading dose of clopidogrel is unknown. Design . In an observational study, 693 consecutive patients were treated with abciximab during percutaneous coronary intervention for ST-elevation myocardial infarction. Totally 354 patients received standard strategy of abciximab bolus and infusion followed by 339 patients that recieved abciximab bolus only (271 patients) or bolus and infusion if suboptimal result (68 patients) in combination with a higher loading dose of clopidogrel (600 mg) – the modified strategy. Results . The two groups were similar regarding baseline characteristics and in hospital bleeding events. At 30 days, the composite of death, re-infarction or target vessel revascularization was 9.1% in the standard and 7.5% in the modified strategy (p = 0.45). The rate of stent thrombosis was lower in the modified strategy group with 0% and 2.3% in the standard group (p < 0.001) and the mean total medical cost was lower in the modified strategy group with €8032 and €8665 in the standard group (p < 0.001). Conclusions . In primary percutaneous coronary intervention with a loading dose of 600 mg clopidogrel, it seems safe and cost-saving to give abciximab bolus with optional infusion.